An Empirical Investigation into the Relationship between Electronic Tax Management System and Tax Revenue Collection Efficiency in Selected States in South West, Nigeria - ADEGBIE, Folajimi Festus; ENERSON, Johnson; OLAOYE, Samuel Adebayo (Archives of Business Research, 2022)
Tax revenue generation in Nigeria has received contemporary discuss and debate in accounting literature and this has aroused great concern for the attainment of sustainable development. The attainment of revenue goals have been adduced to the fact that many issues and challenges faced are multiplicity of taxes, non-availability of database, difficulty in keeping proper track records of tax payers or defaulters, complexity in tax compliance and collection and non-payment of tax refunds amongst others. The study investigated the effect of electronic tax management system on tax revenue collection efficiency. The survey research design was adopted for the study and total enumeration sampling technique was adopted. A total of 2670 copies of structured questionnaires were distributed to respondents across the three selected states to illicit responses while 2199 copies were retrieved back which accounted for 82.4% response rate. Reliability ranged between 0.7 and 0.9. Data were obtained through the use of a well-structured questionnaire. Descriptive and inferential (multiple regression) statistics were used for data analysis. The findings revealed that electronic tax management system measured by Perceived ease of use, internet payment system, mobile payment system and electronic billing machine had a significant impact on the simplicity of filing tax return of tax payers (Adj R2 = 0.113, F-stat = 68.343, p < 0.005). The study concluded that electronic tax management system impacted tax revenue collection efficiency. The study recommended that tax policy makers should ensure that the electronic tax system is designed in such a way that it will make the filing of tax return very simple and will motivate tax payers to pay their taxes and skillful personnel should be made to be in charge of the tax management system.